DEVELOPMENT OF CIBOGO PINTAR GROUP MODELS IN HANDLING CHILDREN'S DROPOUT PROBLEMS OF SCHOOL IN CIBOGO VILLAGE LEMBANG DISTRICT BANDUNG BARAT REGENCY - Pinasti Septhian; Dwi Yuliani; Aep Rusmana (Politeknik Kesejahteraan Sosial Bandung, 2018)
This study aims to Development Model of Kelompok Cibogo Pintar in Handling Drop Out Children Problems in Cibogo Village, Lembang Sub-District, West Bandung Regency. This study used qualitative research method with Participatory Action Research (PAR) design which includes four stages, they are, Early Reflection, Planning, Implementation, and Final Reflection. Researcher used several techniques, i.e interview technique, documentation study, observation, Methode Participation Assessment (MPA), Technic of Participation (TOP), and Focus Group Discussion (FGD) for data collection. Purposive sampling method was used for determining participant. Based on the results of research found several problems experienced by the group and need to be improved 1) Level of Human Resources (knowledge and information), 2) Organizational level (structure, vision, mission, and group meetings), 3) System Level (task-force networking and social networking). Based on the problems of the group and according to the needs of the group, results of the implementation of group development are as follows: 1) the establishment of structure, vision, mission, and monthly routine meetings, 2) increasing knowledge of how to handle dropouts children and the importance of education, 3) increasing information on handling solutions for dropout children, 4) establishment of cooperation with PKBM Jayagiri.